Plant antibacterial composite material and preparation method thereof
The method of preparing porous silicon-based materials with zinc oxide and silicone quaternary ammonium salts through rice husks has solved the problem of inconvenience in disposal of rice husks and pesticide resistance, achieved efficient antibacterial effects, reduced environmental pollution, and improved the safety of agricultural production sex.
Patent Information
- Application Number
- CN202411518893.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2024-12-27
AI Technical Summary
The problem of inconvenient disposal of rice husks and increased pesticide resistance in the prior art has made it difficult to effectively prevent and control diseases in agricultural production, and the utilization efficiency of traditional pesticides is low and environmental pollution is serious.
The porous silicon-based materials are prepared by rice husks, and zinc oxide and silicone quaternary ammonium salts are loaded. Antibacterial composite materials are prepared through high-temperature treatment, acid treatment, zinc nitrate precipitation, hydroxy silicone oil reaction and other steps to achieve stable load and slow release of zinc, and enhance the Antibacterial properties.
It improves the antibacterial activity and stability of antibacterial composite materials, can effectively inhibit the growth and reproduction of various bacteria, reduce the occurrence of diseases, and improves the initial antibacterial properties of the materials through alkali treatment, avoiding environmental pollution of traditional pesticides.
Smart Images

Figure BDA0005107482990000171 
Figure BDA0005107482990000191
Abstract
Description
Technical Field
[0001] The invention belongs to the field of plant protection, and specifically relates to a plant antibacterial composite material and a preparation method thereof. Background Art
[0002] Agricultural production is facing the occurrence of diseases that reduce crop yields and damage quality, causing huge economic losses. Rational application of fertilizers and pesticides can ensure crop yields and solve the problem of food growth for a period of time, but the low utilization rate of traditional fertilizers and the resistance caused by the abuse of pesticides have aggravated the current food crisis.
[0003] Rice husk is the main byproduct of rice processing, accounting for about 20% of the mass of rice. China is the country with the largest rice production and the highest rice husk production. However, rice husk cannot be used on a large scale due to its toughness, low nutritional value and large volume. At present, the two most common methods of rice husk disposal are open-air burning and landfill, which easily lead to energy waste, greenhouse gas emissions, air pollution and occupation of landfill space. Rice husk contains 15-28wt% silica, which is an ideal silicon source. The innovative use of rice husk can not only avoid the negative impact of traditional treatment methods on the environment, but also manufacture various multifunctional carbon-based and silicon-based materials. Silicon can mediate plant disease resistance and effectively reduce the reproduction and infection rate of fungal pathogens. In agricultural plant antibacterial, high-silicon lithium-containing rice husk has great application potential. Summary of the invention
[0004] In order to solve the problems of difficult disposal of rice husks and increased resistance to existing pesticides in the prior art, the present invention mainly provides a plant antibacterial composite material prepared with rice husks as a substrate, and a preparation method of the plant antibacterial composite material, and the technical scheme thereof is as follows:
[0005] A plant antibacterial composite material comprises a porous silicon-based material prepared from rice husks, zinc oxide loaded on the porous silicon-based material, and an organic silicon quaternary ammonium salt grafted on the zinc-loaded silicon-based material.
[0006] Further, the organosilicon quaternary ammonium salt includes one or more of 3-(trimethoxysilylpropyl)dimethyloctadecylammonium chloride, 3-(triethoxysilylpropyl)dimethyloctadecylammonium chloride, 3-(trihydroxysilylpropyl)dimethyloctadecylammonium chloride, 3-(trimethoxysilylpropyl)dimethylhexadecylammonium chloride, 3-(triethoxysilylpropyl)dimethylhexadecylammonium chloride, 3-(trihydroxysilylpropyl)dimethylhexadecylammonium chloride, 3-(trimethoxysilylpropyl)trimethylammonium chloride, 3-(triethoxysilylpropyl)trimethylammonium chloride or 3-(trihydroxysilylpropyl)trimethylammonium chloride.
[0007] A method for preparing the above-mentioned plant antibacterial composite material comprises the following steps: preparing a porous silicon-based material by high-temperature treatment of rice husks, loading zinc on the porous silicon-based material to obtain a zinc-loaded silicon-based material; grafting an organic silicon quaternary ammonium salt onto the zinc-loaded silicon-based material to obtain a surface-treated silicon-based material; and then subjecting the surface-treated silicon-based material to an alkali treatment to obtain an antibacterial composite material.
[0008] Further, the following steps are included:
[0009] a. Calcine the dried rice husk at 550-650°C for 3-5h, and after cooling to room temperature, grind the calcined rice husk into 100-200 meshes to obtain a porous silicon-based material;
[0010] b. Dissolve zinc nitrate in ethanol to prepare a 0.05-0.1 g / mL zinc nitrate solution; place the porous silicon-based material in the zinc nitrate solution, mix thoroughly, and remove bubbles; then add sodium hydroxide, stir at a low speed for 3-5 hours, collect the precipitate, wash it with water, and dry it to obtain a zinc-loaded precursor;
[0011] c. The zinc-loaded precursor obtained in step b is calcined at 400 to 500° C. for 3 to 5 hours to obtain a zinc-loaded silicon-based material;
[0012] d. Dissolve low-viscosity hydroxy silicone oil in ethanol, then add organosilicon quaternary ammonium salt and zinc-loaded silicon-based material, mix thoroughly, and react at 50-70°C for 4-6 hours; collect the precipitate, wash with water and ethanol respectively, and dry to obtain the surface-treated silicon-based material;
[0013] e. Take sodium hydroxide to prepare a sodium hydroxide solution, mix the sodium hydroxide solution with the surface treated silicon-based material, make the mixture fully wet without generating water droplets, steam bath for 1 to 2 hours, and then wash thoroughly with anhydrous alcohol to obtain the antibacterial composite material.
[0014] Furthermore, the mass ratio of the zinc nitrate to the porous silicon-based material in step b is 1:(2.5-3.5); the molar ratio of the zinc nitrate to sodium hydroxide in step b is 1:(1.1-1.3).
[0015] Furthermore, the low-speed stirring in step b is stirring at a speed of 100 to 200 r / min.
[0016] Furthermore, the mass ratio of the hydroxy silicone oil in step d to the zinc-loaded silicon-based material is 1:(1.5-3.5); the mass ratio of the organosilicon quaternary ammonium salt in step d to the zinc-loaded silicon-based material is 1:(3-8).
[0017] Furthermore, the concentration of the sodium hydroxide solution in step e is 2-3 mol / L.
[0018] Furthermore, before the rice husk is subjected to high-temperature treatment, it is first subjected to acid treatment, which specifically includes the following steps: after the rice husk is crushed, it is placed in hydrochloric acid with a concentration of 2 to 2.5 mol / L and fully dispersed, and then allowed to stand for 5 to 8 hours; after washing with water until the pH value no longer changes, it is dried to complete the acid treatment; the mass ratio of the rice husk to the hydrochloric acid is 1:(8 to 10).
[0019] A plant antibacterial preparation using the plant antibacterial composite material.
[0020] By adopting the above scheme, the method of the present invention has the following advantages:
[0021] 1. The zinc oxide loaded on the antibacterial composite material of the present invention has strong antibacterial activity, can generate active oxygen, and has excellent antibacterial activity against a wide range of bacteria. In addition, the zinc ions generated by deliquescence during use interact with substances in cells to produce further antibacterial effects on pathogens.
[0022] 2. The present invention uses rice husks to prepare a silicon-based material with a high silicon content and high porosity, which can inhibit the energy metabolism and synthesis of growth substances of pathogens, inhibit the growth and development of bacteria and the formation of sclerotia, and has good antibacterial properties.
[0023] 3. The silicon-based material of the present invention has a large specific surface area, and zinc oxide and unreacted zinc hydroxide are dispersed in the pores of the silicon-based material. The porous silicon-based material serves as an excellent carrier of antibacterial materials, which can promote the slow and uniform release of zinc and improve the stability of antibacterial active substances such as zinc.
[0024] 4. The present invention uses ethanol-soluble zinc nitrate to fully infiltrate the internal pores of the porous silicon-based material, and then generates insoluble zinc hydroxide under the action of sodium hydroxide, which is retained in the pores, and then calcined to obtain zinc oxide, thereby achieving stable loading of zinc oxide.
[0025] 5. The present invention grafts the antibacterial agent onto the silicon-based material matrix skeleton through covalent bonds, so that the organosilicon quaternary ammonium salt is fixed in the zinc-loaded silicon-based material structure, preventing the quaternary ammonium salt from falling off from the silicon-based material, thereby improving the durability of the antibacterial composite material.
[0026] 6. The present invention uses alkali for surface treatment to generate silicate on the surface of the silicon-based material, making the silicon on the surface soluble and able to penetrate deep into the bacteria, thus producing strong antibacterial properties at the initial stage of use, compensating for the antibacterial window caused by the low initial concentration of the composite material, and forming rapid antibacterial properties for plants that have already developed diseases.
[0027] 7. The present invention performs acid treatment on rice husks, so that the subsequent calcination of the rice husks is more complete, the content of other substances remaining in the silicon-based material except silicon is reduced, the calcination is more thorough, and the pores are formed more fully. DETAILED DESCRIPTION
[0028] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] Example 1: (1) After the rice husk is crushed, it is placed in hydrochloric acid with a concentration of 2 to 2.5 mol / L at a mass ratio of 1:8 and fully dispersed, and then allowed to stand for 8 hours; after washing with water until the pH value no longer changes, it is dried, and the acid treatment is completed;
[0030] (2) calcining the dried rice husk at 600°C for 4 hours, and then grinding the calcined rice husk into 100-200 meshes after cooling to room temperature to obtain a porous silicon-based material;
[0031] (3) Dissolving zinc nitrate in ethanol to prepare a 0.05 g / mL zinc nitrate solution; placing a porous silicon-based material 2.5 times the mass of the zinc nitrate in the zinc nitrate solution, mixing thoroughly, and removing bubbles; then adding sodium hydroxide 1.2 times the mass of the zinc nitrate, stirring at 100 r / min for 3 hours, collecting the precipitate, washing with water, and drying to obtain a zinc-loaded precursor;
[0032] (4) calcining the zinc-loaded precursor obtained in step b at 450° C. for 4 h to obtain a zinc-loaded silicon-based material;
[0033] (5) taking 3-(trimethoxysilylpropyl)dimethyloctadecylammonium chloride and zinc-loaded silicon-based material in a mass ratio of 1:3, dissolving 0.3 times the mass of the zinc-loaded silicon-based material in low-viscosity hydroxy silicone oil in ethanol, fully mixing 3-(trimethoxysilylpropyl)dimethyloctadecylammonium chloride, the zinc-loaded silicon-based material and the hydroxy silicone oil solution, and reacting at 60° C. for 4 hours; collecting the precipitate, washing it with water and ethanol respectively, and drying it to obtain the surface-treated silicon-based material;
[0034] (6) Using sodium hydroxide to prepare a 2-3 mol / L sodium hydroxide solution, mixing the sodium hydroxide solution with the surface-treated silicon-based material to make the mixture fully wet without generating water droplets, steam bathing for 1 hour, and then washing with anhydrous alcohol to obtain an antibacterial composite material.
[0035] Example 2: (1) After the rice husk is crushed, it is placed in a hydrochloric acid with a concentration of 2 to 2.5 mol / L at a mass ratio of 1:10 and fully dispersed, and then allowed to stand for 8 hours; after washing with water until the pH value no longer changes, it is dried, and the acid treatment is completed;
[0036] (2) calcining the dried rice husk at 600°C for 4 hours, and then grinding the calcined rice husk into 100-200 meshes after cooling to room temperature to obtain a porous silicon-based material;
[0037] (3) Dissolving zinc nitrate in ethanol to prepare a 0.05 g / mL zinc nitrate solution; placing a porous silicon-based material 2.5 times the mass of the zinc nitrate in the zinc nitrate solution, mixing thoroughly, and removing bubbles; then adding sodium hydroxide 1.2 times the mass of the zinc nitrate, stirring at 100 r / min for 3 hours, collecting the precipitate, washing with water, and drying to obtain a zinc-loaded precursor;
[0038] (4) calcining the zinc-loaded precursor obtained in step b at 450° C. for 4 h to obtain a zinc-loaded silicon-based material;
[0039] (5) taking 3-(trimethoxysilylpropyl)dimethyloctadecylammonium chloride and zinc-loaded silicon-based material in a mass ratio of 1:3, dissolving 0.3 times the mass of the zinc-loaded silicon-based material in low-viscosity hydroxy silicone oil in ethanol, fully mixing 3-(trimethoxysilylpropyl)dimethyloctadecylammonium chloride, the zinc-loaded silicon-based material and the hydroxy silicone oil solution, and reacting at 60° C. for 4 hours; collecting the precipitate, washing it with water and ethanol respectively, and drying it to obtain the surface-treated silicon-based material;
[0040] (6) Using sodium hydroxide to prepare a 2-3 mol / L sodium hydroxide solution, mixing the sodium hydroxide solution with the surface-treated silicon-based material to make the mixture fully wet without generating water droplets, steam bathing for 1 hour, and then washing with anhydrous alcohol to obtain an antibacterial composite material.
[0041] Example 3: (1) After the rice husk is crushed, it is placed in hydrochloric acid with a concentration of 2 to 2.5 mol / L at a mass ratio of 1:8 and fully dispersed, and then allowed to stand for 8 hours; washed with water until the pH value no longer changes, and then dried, thereby completing the acid treatment;
[0042] (2) calcining the dried rice husk at 600°C for 4 hours, and then grinding the calcined rice husk into 100-200 meshes after cooling to room temperature to obtain a porous silicon-based material;
[0043] (3) Dissolving zinc nitrate in ethanol to prepare a 0.1 g / mL zinc nitrate solution; placing a porous silicon-based material 2.5 times the mass of the zinc nitrate in the zinc nitrate solution, mixing thoroughly, and removing bubbles; then adding sodium hydroxide 1.2 times the mass of the zinc nitrate, stirring at 100 r / min for 3 hours, collecting the precipitate, washing with water, and drying to obtain a zinc-loaded precursor;
[0044] (4) calcining the zinc-loaded precursor obtained in step b at 450° C. for 4 h to obtain a zinc-loaded silicon-based material;
[0045] (5) taking 3-(trimethoxysilylpropyl)dimethyloctadecylammonium chloride and zinc-loaded silicon-based material in a mass ratio of 1:3, dissolving 0.3 times the mass of the zinc-loaded silicon-based material in low-viscosity hydroxy silicone oil in ethanol, fully mixing 3-(trimethoxysilylpropyl)dimethyloctadecylammonium chloride, the zinc-loaded silicon-based material and the hydroxy silicone oil solution, and reacting at 60° C. for 4 hours; collecting the precipitate, washing it with water and ethanol respectively, and drying it to obtain the surface-treated silicon-based material;
[0046] (6) Using sodium hydroxide to prepare a 2-3 mol / L sodium hydroxide solution, mixing the sodium hydroxide solution with the surface-treated silicon-based material to make the mixture fully wet without generating water droplets, steam bathing for 1 hour, and then washing with anhydrous alcohol to obtain an antibacterial composite material.
[0047] Example 4: (1) After the rice husk is crushed, it is placed in hydrochloric acid with a concentration of 2 to 2.5 mol / L at a mass ratio of 1:8 and fully dispersed, and then allowed to stand for 8 hours; after washing with water until the pH value no longer changes, it is dried, and the acid treatment is completed;
[0048] (2) calcining the dried rice husk at 600°C for 4 hours, and then grinding the calcined rice husk into 100-200 meshes after cooling to room temperature to obtain a porous silicon-based material;
[0049] (3) Dissolving zinc nitrate in ethanol to prepare a 0.05 g / mL zinc nitrate solution; placing a porous silicon-based material 3.5 times the mass of the zinc nitrate in the zinc nitrate solution, mixing thoroughly, and removing bubbles; then adding sodium hydroxide 1.2 times the mass of the zinc nitrate, stirring at 100 r / min for 3 hours, collecting the precipitate, washing with water, and drying to obtain a zinc-loaded precursor;
[0050] (4) calcining the zinc-loaded precursor obtained in step b at 450° C. for 4 h to obtain a zinc-loaded silicon-based material;
[0051] (5) taking 3-(trimethoxysilylpropyl)dimethyloctadecylammonium chloride and zinc-loaded silicon-based material in a mass ratio of 1:3, dissolving 0.3 times the mass of the zinc-loaded silicon-based material in low-viscosity hydroxy silicone oil in ethanol, fully mixing 3-(trimethoxysilylpropyl)dimethyloctadecylammonium chloride, the zinc-loaded silicon-based material and the hydroxy silicone oil solution, and reacting at 60° C. for 4 hours; collecting the precipitate, washing it with water and ethanol respectively, and drying it to obtain the surface-treated silicon-based material;
[0052] (6) Using sodium hydroxide to prepare a 2-3 mol / L sodium hydroxide solution, mixing the sodium hydroxide solution with the surface-treated silicon-based material to make the mixture fully wet without generating water droplets, steam bathing for 1 hour, and then washing with anhydrous alcohol to obtain an antibacterial composite material.
[0053] Example 5: (1) After the rice husk is crushed, it is placed in a hydrochloric acid with a concentration of 2 to 2.5 mol / L at a mass ratio of 1:8 and fully dispersed, and then allowed to stand for 8 hours; after washing with water until the pH value no longer changes, it is dried, and the acid treatment is completed;
[0054] (2) calcining the dried rice husk at 600°C for 4 hours, and then grinding the calcined rice husk into 100-200 meshes after cooling to room temperature to obtain a porous silicon-based material;
[0055] (3) Dissolving zinc nitrate in ethanol to prepare a 0.05 g / mL zinc nitrate solution; placing a porous silicon-based material 2.5 times the mass of the zinc nitrate in the zinc nitrate solution, mixing thoroughly, and removing bubbles; then adding sodium hydroxide 1.2 times the mass of the zinc nitrate, stirring at 200 r / min for 3 hours, collecting the precipitate, washing with water, and drying to obtain a zinc-loaded precursor;
[0056] (4) calcining the zinc-loaded precursor obtained in step b at 450° C. for 4 h to obtain a zinc-loaded silicon-based material;
[0057] (5) taking 3-(trimethoxysilylpropyl)dimethyloctadecylammonium chloride and zinc-loaded silicon-based material in a mass ratio of 1:3, dissolving 0.3 times the mass of the zinc-loaded silicon-based material in low-viscosity hydroxy silicone oil in ethanol, fully mixing 3-(trimethoxysilylpropyl)dimethyloctadecylammonium chloride, the zinc-loaded silicon-based material and the hydroxy silicone oil solution, and reacting at 60° C. for 4 hours; collecting the precipitate, washing it with water and ethanol respectively, and drying it to obtain the surface-treated silicon-based material;
[0058] (6) Using sodium hydroxide to prepare a 2-3 mol / L sodium hydroxide solution, mixing the sodium hydroxide solution with the surface-treated silicon-based material to make the mixture fully wet without generating water droplets, steam bathing for 1 hour, and then washing with anhydrous alcohol to obtain an antibacterial composite material.
[0059] Example 6: (1) After the rice husk is crushed, it is placed in a hydrochloric acid with a concentration of 2 to 2.5 mol / L at a mass ratio of 1:8 and fully dispersed, and then allowed to stand for 8 hours; after washing with water until the pH value no longer changes, it is dried, and the acid treatment is completed;
[0060] (2) calcining the dried rice husk at 600°C for 4 hours, and then grinding the calcined rice husk into 100-200 meshes after cooling to room temperature to obtain a porous silicon-based material;
[0061] (3) Dissolving zinc nitrate in ethanol to prepare a 0.05 g / mL zinc nitrate solution; placing a porous silicon-based material 2.5 times the mass of the zinc nitrate in the zinc nitrate solution, mixing thoroughly, and removing bubbles; then adding sodium hydroxide 1.2 times the mass of the zinc nitrate, stirring at a speed of 100 r / min for 5 hours, collecting the precipitate, washing with water, and drying to obtain a zinc-loaded precursor;
[0062] (4) calcining the zinc-loaded precursor obtained in step b at 450° C. for 4 h to obtain a zinc-loaded silicon-based material;
[0063] (5) taking 3-(trimethoxysilylpropyl)dimethyloctadecylammonium chloride and zinc-loaded silicon-based material in a mass ratio of 1:3, dissolving 0.3 times the mass of the zinc-loaded silicon-based material in low-viscosity hydroxy silicone oil in ethanol, fully mixing 3-(trimethoxysilylpropyl)dimethyloctadecylammonium chloride, the zinc-loaded silicon-based material and the hydroxy silicone oil solution, and reacting at 60° C. for 4 hours; collecting the precipitate, washing it with water and ethanol respectively, and drying it to obtain the surface-treated silicon-based material;
[0064] (6) Using sodium hydroxide to prepare a 2-3 mol / L sodium hydroxide solution, mixing the sodium hydroxide solution with the surface-treated silicon-based material to make the mixture fully wet without generating water droplets, steam bathing for 1 hour, and then washing with anhydrous alcohol to obtain an antibacterial composite material.
[0065] Example 7: (1) After the rice husk is crushed, it is placed in a hydrochloric acid with a concentration of 2 to 2.5 mol / L at a mass ratio of 1:8 and fully dispersed, and then allowed to stand for 8 hours; after washing with water until the pH value no longer changes, it is dried, and the acid treatment is completed;
[0066] (2) calcining the dried rice husk at 600°C for 4 hours, and then grinding the calcined rice husk into 100-200 meshes after cooling to room temperature to obtain a porous silicon-based material;
[0067] (3) Dissolving zinc nitrate in ethanol to prepare a 0.05 g / mL zinc nitrate solution; placing a porous silicon-based material 2.5 times the mass of the zinc nitrate in the zinc nitrate solution, mixing thoroughly, and removing bubbles; then adding sodium hydroxide 1.2 times the mass of the zinc nitrate, stirring at 100 r / min for 3 hours, collecting the precipitate, washing with water, and drying to obtain a zinc-loaded precursor;
[0068] (4) calcining the zinc-loaded precursor obtained in step b at 450° C. for 4 h to obtain a zinc-loaded silicon-based material;
[0069] (5) taking 3-(trimethoxysilylpropyl)dimethyloctadecylammonium chloride and zinc-loaded silicon-based material in a mass ratio of 1:8, dissolving 0.3 times the mass of the zinc-loaded silicon-based material in low-viscosity hydroxy silicone oil in ethanol, fully mixing 3-(trimethoxysilylpropyl)dimethyloctadecylammonium chloride, the zinc-loaded silicon-based material and the hydroxy silicone oil solution, and reacting at 60° C. for 4 hours; collecting the precipitate, washing it with water and ethanol respectively, and drying it to obtain the surface-treated silicon-based material;
[0070] (6) Using sodium hydroxide to prepare a 2-3 mol / L sodium hydroxide solution, mixing the sodium hydroxide solution with the surface-treated silicon-based material to make the mixture fully wet without generating water droplets, steam bathing for 1 hour, and then washing with anhydrous alcohol to obtain an antibacterial composite material.
[0071] Example 8: (1) After the rice husk is crushed, it is placed in hydrochloric acid with a concentration of 2 to 2.5 mol / L at a mass ratio of 1:8 and fully dispersed, and then allowed to stand for 8 hours; washed with water until the pH value no longer changes, and then dried, thereby completing the acid treatment;
[0072] (2) calcining the dried rice husk at 600°C for 4 hours, and then grinding the calcined rice husk into 100-200 meshes after cooling to room temperature to obtain a porous silicon-based material;
[0073] (3) Dissolving zinc nitrate in ethanol to prepare a 0.05 g / mL zinc nitrate solution; placing a porous silicon-based material 2.5 times the mass of the zinc nitrate in the zinc nitrate solution, mixing thoroughly, and removing bubbles; then adding sodium hydroxide 1.2 times the mass of the zinc nitrate, stirring at 100 r / min for 3 hours, collecting the precipitate, washing with water, and drying to obtain a zinc-loaded precursor;
[0074] (4) calcining the zinc-loaded precursor obtained in step b at 450° C. for 4 h to obtain a zinc-loaded silicon-based material;
[0075] (5) taking 3-(trimethoxysilylpropyl)dimethyloctadecylammonium chloride and zinc-loaded silicon-based material in a mass ratio of 1:3, dissolving 0.6 times the mass of the zinc-loaded silicon-based material in low-viscosity hydroxy silicone oil in ethanol, fully mixing 3-(trimethoxysilylpropyl)dimethyloctadecylammonium chloride, the zinc-loaded silicon-based material and the hydroxy silicone oil solution, and reacting at 60° C. for 4 hours; collecting the precipitate, washing it with water and ethanol respectively, and drying it to obtain the surface-treated silicon-based material;
[0076] (6) Using sodium hydroxide to prepare a 2-3 mol / L sodium hydroxide solution, mixing the sodium hydroxide solution with the surface-treated silicon-based material to make the mixture fully wet without generating water droplets, steam bathing for 1 hour, and then washing with anhydrous alcohol to obtain an antibacterial composite material.
[0077] Example 9: (1) After the rice husk is crushed, it is placed in hydrochloric acid with a concentration of 2 to 2.5 mol / L at a mass ratio of 1:8 and fully dispersed, and then allowed to stand for 8 hours; after washing with water until the pH value no longer changes, it is dried, and the acid treatment is completed;
[0078] (2) calcining the dried rice husk at 600°C for 4 hours, and then grinding the calcined rice husk into 100-200 meshes after cooling to room temperature to obtain a porous silicon-based material;
[0079] (3) Dissolving zinc nitrate in ethanol to prepare a 0.05 g / mL zinc nitrate solution; placing a porous silicon-based material 2.5 times the mass of the zinc nitrate in the zinc nitrate solution, mixing thoroughly, and removing bubbles; then adding sodium hydroxide 1.2 times the mass of the zinc nitrate, stirring at 100 r / min for 3 hours, collecting the precipitate, washing with water, and drying to obtain a zinc-loaded precursor;
[0080] (4) calcining the zinc-loaded precursor obtained in step b at 450° C. for 4 h to obtain a zinc-loaded silicon-based material;
[0081] (5) taking 3-(trimethoxysilylpropyl)dimethyloctadecylammonium chloride and zinc-loaded silicon-based material in a mass ratio of 1:3, dissolving 0.3 times the mass of the zinc-loaded silicon-based material in low-viscosity hydroxy silicone oil in ethanol, fully mixing 3-(trimethoxysilylpropyl)dimethyloctadecylammonium chloride, the zinc-loaded silicon-based material and the hydroxy silicone oil solution, and reacting at 60° C. for 6 hours; collecting the precipitate, washing it with water and ethanol respectively, and drying it to obtain the surface-treated silicon-based material;
[0082] (6) Using sodium hydroxide to prepare a 2-3 mol / L sodium hydroxide solution, mixing the sodium hydroxide solution with the surface-treated silicon-based material to make the mixture fully wet without generating water droplets, steam bathing for 1 hour, and then washing with anhydrous alcohol to obtain an antibacterial composite material.
[0083] Example 10: (1) After the rice husk is crushed, it is placed in hydrochloric acid with a concentration of 2 to 2.5 mol / L at a mass ratio of 1:8 and fully dispersed, and then allowed to stand for 8 hours; after washing with water until the pH value no longer changes, it is dried, and the acid treatment is completed;
[0084] (2) calcining the dried rice husk at 600°C for 4 hours, and then grinding the calcined rice husk into 100-200 meshes after cooling to room temperature to obtain a porous silicon-based material;
[0085] (3) Dissolving zinc nitrate in ethanol to prepare a 0.05 g / mL zinc nitrate solution; placing a porous silicon-based material 2.5 times the mass of the zinc nitrate in the zinc nitrate solution, mixing thoroughly, and removing bubbles; then adding sodium hydroxide 1.2 times the mass of the zinc nitrate, stirring at 100 r / min for 3 hours, collecting the precipitate, washing with water, and drying to obtain a zinc-loaded precursor;
[0086] (4) calcining the zinc-loaded precursor obtained in step b at 450° C. for 4 h to obtain a zinc-loaded silicon-based material;
[0087] (5) taking 3-(trimethoxysilylpropyl)dimethyloctadecylammonium chloride and zinc-loaded silicon-based material in a mass ratio of 1:3, dissolving 0.3 times the mass of the zinc-loaded silicon-based material in low-viscosity hydroxy silicone oil in ethanol, fully mixing 3-(trimethoxysilylpropyl)dimethyloctadecylammonium chloride, the zinc-loaded silicon-based material and the hydroxy silicone oil solution, and reacting at 60° C. for 4 hours; collecting the precipitate, washing it with water and ethanol respectively, and drying it to obtain the surface-treated silicon-based material;
[0088] (6) Sodium hydroxide is used to prepare a 2-3 mol / L sodium hydroxide solution, and the sodium hydroxide solution is mixed with the surface-treated silicon-based material to make the mixture fully wet without generating water droplets. After a steam bath for 2 hours, the mixture is fully washed with anhydrous alcohol to obtain an antibacterial composite material.
[0089] Comparative Example 1: (1) After the rice husk is crushed, it is placed in a hydrochloric acid with a concentration of 2 to 2.5 mol / L at a mass ratio of 1:8 and fully dispersed, and then allowed to stand for 8 hours; after washing with water until the pH value no longer changes, it is dried, and the acid treatment is completed;
[0090] (2) calcining the dried rice husk at 600°C for 4 hours, and then grinding the calcined rice husk into 100-200 meshes after cooling to room temperature to obtain a porous silicon-based material;
[0091] (3) Dissolving zinc nitrate in ethanol to prepare a 0.05 g / mL zinc nitrate solution; placing a porous silicon-based material 2.5 times the mass of the zinc nitrate in the zinc nitrate solution, mixing thoroughly, and removing bubbles; then adding sodium hydroxide 1.2 times the mass of the zinc nitrate, stirring at 100 r / min for 3 hours, collecting the precipitate, washing with water, and drying to obtain a zinc-loaded precursor;
[0092] (4) calcining the zinc-loaded precursor obtained in step b at 450° C. for 4 h to obtain a zinc-loaded silicon-based material;
[0093] (5) Take 3-(trimethoxysilylpropyl)dimethyloctadecylammonium chloride and zinc-loaded silicon-based material in a mass ratio of 1:3, dissolve 0.3 times the mass of low-viscosity hydroxy silicone oil of the zinc-loaded silicon-based material in ethanol, fully mix 3-(trimethoxysilylpropyl)dimethyloctadecylammonium chloride, zinc-loaded silicon-based material and hydroxy silicone oil solution, and react at 60° C. for 4 hours; collect the precipitate, wash with water and ethanol respectively, and dry to obtain the product.
[0094] Comparative Example 2: (1) After the rice husk is crushed, it is placed in a hydrochloric acid with a concentration of 2 to 2.5 mol / L at a mass ratio of 1:8 and fully dispersed, and then allowed to stand for 8 hours; after washing with water until the pH value no longer changes, it is dried, and the acid treatment is completed;
[0095] (2) calcining the dried rice husk at 600°C for 4 hours, and then grinding the calcined rice husk into 100-200 meshes after cooling to room temperature to obtain a porous silicon-based material;
[0096] (3) Dissolving zinc nitrate in ethanol to prepare a 0.05 g / mL zinc nitrate solution; placing a porous silicon-based material 2.5 times the mass of the zinc nitrate in the zinc nitrate solution, mixing thoroughly, and removing bubbles; then adding sodium hydroxide 1.2 times the mass of the zinc nitrate, stirring at 100 r / min for 3 hours, collecting the precipitate, washing with water, and drying to obtain a zinc-loaded precursor;
[0097] (4) calcining the zinc-loaded precursor obtained in step b at 450° C. for 4 h to obtain a zinc-loaded silicon-based material;
[0098] (5) Using sodium hydroxide to prepare a 2-3 mol / L sodium hydroxide solution, mixing the sodium hydroxide solution with the zinc-supported silicon-based material to make the mixture fully wet without generating water droplets, steam bathing for 1 hour, and then washing with anhydrous alcohol to obtain an antibacterial composite material.
[0099] Comparative Example 3: (1) After the rice husk is crushed, it is placed in a hydrochloric acid with a concentration of 2 to 2.5 mol / L at a mass ratio of 1:8 and fully dispersed, and then allowed to stand for 8 hours; after washing with water until the pH value no longer changes, it is dried, and the acid treatment is completed;
[0100] (2) calcining the dried rice husk at 600°C for 4 hours, and then grinding the calcined rice husk into 100-200 meshes after cooling to room temperature to obtain a porous silicon-based material;
[0101] (3) taking 3-(trimethoxysilylpropyl)dimethyloctadecylammonium chloride and porous silicon-based material in a mass ratio of 1:3, dissolving 0.3 times the mass of the porous silicon-based material in low-viscosity hydroxy silicone oil in ethanol, fully mixing 3-(trimethoxysilylpropyl)dimethyloctadecylammonium chloride, zinc-loaded silicon-based material and hydroxy silicone oil solution, and reacting at 60° C. for 4 h; collecting the precipitate, washing with water and ethanol respectively, and drying to obtain the surface-treated silicon-based material;
[0102] (4) preparing a 2-3 mol / L sodium hydroxide solution with sodium hydroxide, mixing the sodium hydroxide solution with the surface-treated silicon-based material to make the mixture fully wet without generating water droplets, steaming for 1 hour, and then washing with anhydrous alcohol to obtain an antibacterial composite material.
[0103] Example sample test:
[0104] The mycelium linear growth rate method of GB / T38480-2020 was used, and the mass concentration of the antimicrobial agent was 50 mg / L, using a xenon lamp (light intensity of 9×10 4The samples were irradiated with 100 lux for 45 minutes and then placed in a constant temperature incubator for culture. The inhibition rates of each embodiment and comparative example on Sclerotinia sclerotiorum and Fusarium oxysporum were determined to evaluate the in vitro inhibitory activity of each antibacterial agent. The results are as follows:
[0105]
[0106] As can be seen from the above table, the inhibition rates of various embodiments of the present invention on Sclerotinia and Fusarium oxysporum are maintained at more than 75%, and the inhibition rates of most embodiments are more than 90%. The antibacterial composite material of the present invention has a significant antibacterial effect. Example 2 uses more hydrochloric acid for acid treatment than Example 1, and the inhibition rates of both pathogens are increased, indicating that more thorough acid treatment can improve the antibacterial activity of porous silicon-based materials, which may be due to fewer impurities after treatment. The concentration of zinc nitrate in Example 3 is higher than that in Example 1, and the inhibition rate of pathogens is also increased. It may be that a higher concentration is more conducive to the deposition of zinc in porous silicon-based materials. Compared with Example 1, Example 4 has a larger amount of porous silicon-based materials added, and the inhibition rates of the two pathogens are significantly reduced, indicating that the amount of zinc loaded has a significant effect on the antibacterial properties of the antibacterial composite material. In the process of zinc loading, compared with Example 1, the stirring speed of Example 5 is faster, and the inhibition rate decreases. It may be that the faster stirring speed easily causes the precipitation of the load in the pores of the porous silicon-based material to escape, affecting the antibacterial ability, while the stirring time of Example 6 is longer, and the inhibition rate increases, indicating that more reaction time is conducive to the stable loading of zinc. In Comparative Example 3, no zinc loading was performed, and the inhibition rates of Sclerotinia sclerotiorum and Fusarium oxysporum were significantly reduced.
[0107] In Example 7, the amount of organosilicon quaternary ammonium salt added is less than that in Example 1, and the inhibition rate decreases. In Example 8, the amount of hydroxy silicone oil added is increased, and the inhibition rate increases. In Example 9, the reaction time is longer, and the inhibition rate also increases. On the contrary, in Comparative Example 2, the organosilicon quaternary ammonium salt is not grafted, and the inhibition rate decreases significantly, indicating that the more the organosilicon quaternary ammonium salt is grafted, the better the antibacterial effect of the antibacterial composite material. In Example 10, the steam bath time is longer during the alkali treatment, and the inhibition effect on Sclerotinia sclerotiorum and Fusarium oxysporum is enhanced, indicating that the silicon ions produced by the alkali treatment can significantly increase the antibacterial properties of the antibacterial composite material. Comparative Example 1 did not undergo alkali treatment, and its inhibition rate on pathogens decreased significantly.
[0108] The mycelium dry weight method was used to determine the sustained inhibitory effect of each embodiment and comparative example on Aspergillus flavus. 6The spore suspension of CFU / mlL was inoculated into the PDB liquid culture medium containing the antibacterial composite material of each embodiment and comparative example at a concentration of 100 mg / L. The culture was carried out at 28°C, 120 r / min rotation speed, and light. The control group without antibacterial agent was used, and the dry weight of mycelium was weighed once at 6h, 12h, 24h, 42h, and 72h. The difference between each weighing time and the initial dry weight was calculated, and the antibacterial rate of each embodiment and comparative example antibacterial agent sample was calculated using the following formula:
[0109] Bacterial inhibition rate = (dry weight difference of control group - dry weight difference of test sample) / dry weight difference of control group. The results are as follows:
[0110]
[0111] As can be seen from the above table, each embodiment of the present invention has a long inhibition time on Aspergillus flavus. Among them, Example 2 with a longer acid treatment time, Example 3 with a higher zinc nitrate concentration, and Example 6 with a longer stirring time can all maintain an inhibition rate of more than 80% within 72h, indicating that the stable loading of zinc is conducive to the maintenance of the inhibition rate and the realization of long-term inhibition. Example 8 and Example 9 also have good antibacterial time, indicating that sufficient hydroxy silicone oil and reaction time are conducive to the full grafting of organosilicon quaternary ammonium salts, improving the durability of the antibacterial composite material of the present invention. The steam bath time of Example 10 is long, and the sample has a good inhibition rate of Aspergillus flavus in the early stage, but the inhibition rate drops rapidly in the later stage. It may be that the longer alkali treatment time is easy to affect the skeleton of the antibacterial composite material, which is not conducive to the loading of antibacterial active substances such as zinc, and is easy to affect the sustained release effect of the material. The initial inhibition rate of Comparative Example 1 without alkali treatment is inferior to that of each comparative example, indicating that the alkali treatment step can ensure the initial antibacterial effect of the antibacterial composite material.
[0112] For those skilled in the art, various other corresponding changes and deformations can be made according to the technical solutions and concepts described above, and all of these changes and deformations should fall within the protection scope of the claims of the present invention.
Claims
1. A plant antibacterial composite material, characterized in that: The invention comprises a porous silicon-based material prepared from rice husk, zinc oxide loaded on the porous silicon-based material, and an organic silicon quaternary ammonium salt grafted on the zinc-loaded silicon-based material.
2. The plant antibacterial composite material according to claim 1, characterized in that: The organosilicon quaternary ammonium salt includes one or more of 3-(trimethoxysilylpropyl)dimethyloctadecylammonium chloride, 3-(triethoxysilylpropyl)dimethyloctadecylammonium chloride, 3-(trihydroxysilylpropyl)dimethyloctadecylammonium chloride, 3-(trimethoxysilylpropyl)dimethylhexadecylammonium chloride, 3-(triethoxysilylpropyl)dimethylhexadecylammonium chloride, 3-(trihydroxysilylpropyl)dimethylhexadecylammonium chloride, 3-(trimethoxysilylpropyl)trimethylammonium chloride, 3-(triethoxysilylpropyl)trimethylammonium chloride or 3-(trihydroxysilylpropyl)trimethylammonium chloride.
3. A method for preparing the plant antibacterial composite material according to claim 1, characterized in that: The method comprises the following steps: preparing a porous silicon-based material by subjecting rice husk to high-temperature treatment, loading zinc on the porous silicon-based material to obtain a zinc-loaded silicon-based material; grafting an organic silicon quaternary ammonium salt onto the zinc-loaded silicon-based material to obtain a surface-treated silicon-based material; and then subjecting the surface-treated silicon-based material to an alkali treatment to obtain an antibacterial composite material.
4. The method for preparing the plant antibacterial composite material according to claim 3, characterized in that: The following steps are involved: a. Calcine the dried rice husk at 550-650°C for 3-5h, and after cooling to room temperature, grind the calcined rice husk into 100-200 meshes to obtain a porous silicon-based material; b. Dissolve zinc nitrate in ethanol to prepare a 0.05-0.1 g / mL zinc nitrate solution; place the porous silicon-based material in the zinc nitrate solution, mix thoroughly, and remove bubbles; then add sodium hydroxide, stir at a low speed for 3-5 hours, collect the precipitate, wash it with water, and dry it to obtain a zinc-loaded precursor; c. The zinc-loaded precursor obtained in step b is calcined at 400 to 500° C. for 3 to 5 hours to obtain a zinc-loaded silicon-based material; d. Dissolve low-viscosity hydroxy silicone oil in ethanol, then add organosilicon quaternary ammonium salt and zinc-supported silicon-based material, mix thoroughly, and react at 50-70°C for 4-6 hours; The precipitate is collected, washed with water and ethanol respectively, and dried to obtain the surface-treated silicon-based material; e. Take sodium hydroxide to prepare a sodium hydroxide solution, mix the sodium hydroxide solution with the surface treated silicon-based material, make the mixture fully wet without generating water droplets, steam bath for 1 to 2 hours, and then wash thoroughly with anhydrous alcohol to obtain the antibacterial composite material.
5. The method for preparing the plant antibacterial composite material according to claim 4, characterized in that: The mass ratio of zinc nitrate to porous silicon-based material in step b is 1: (2.5~3.5); the molar ratio of zinc nitrate to sodium hydroxide in step b is 1:(1.1~1.3).
6. The method for preparing the plant antibacterial composite material according to claim 4, characterized in that: The low-speed stirring in step b is stirring at a speed of 100 to 200 r / min.
7. The method for preparing the plant antibacterial composite material according to claim 4, characterized in that: The mass ratio of the hydroxy silicone oil to the zinc-carrying silicon-based material in step d is 1: (1.5~3.5); The mass ratio of the organosilicon quaternary ammonium salt to the zinc-supported silicon-based material in step d is 1:(3~8).
8. The method for preparing the plant antibacterial composite material according to claim 4, characterized in that: The concentration of the sodium hydroxide solution in step e is 2-3 mol / L.
9. The method for preparing the plant antibacterial composite material according to claim 4, characterized in that: Before the rice husk is subjected to high-temperature treatment, an acid treatment is first performed, which specifically includes the following steps: the rice husk is crushed, placed in hydrochloric acid with a concentration of 2 to 2.5 mol / L to be fully dispersed, and then allowed to stand for 5 to 8 hours; washed with water until the pH value no longer changes, and then dried to complete the acid treatment; the mass ratio of the rice husk to the hydrochloric acid is 1:(8 to 10).
10. A plant antibacterial preparation using the plant antibacterial composite material according to claim 1.
